Realities of community participation in metropolitan planning in Bangladesh: A comparative study of citizens and planning practitioners’ perceptions - Swapan, Mohammad (Elsevier, 2014)
Despite the axiomatic desirability of community participation in planning within developing countries,citizens’ motivation and participation in planning projects has remained consistently low. The paperexamines reasons behind low-level of participation in developing countries by considering citizen andpractitioners’ perceptions. The study reports on the interviews of the citizens in Dhaka, Bangladesh. Theempirical study identifies social-cultural factors that directly determine individual’s tendency includingindividual’s lack of awareness, discouraging perceptions about participation outcomes and most notablylack of trust in the planning system. A comparative picture of citizens and practitioners’ viewpoints,however, indicate a gap between their perceptions in terms of highlighting the most important factor.This suggests that there could be significant improvement in the extent and effectiveness of communityparticipation by motivating practitioners to the need to be more critical of and accountable for theirdealings with the community.